PENGARUH PENERAPAN GAYA MENGAJAR KOMANDO TERHADAP KEMAMPUAN GERAK DASAR MENENDANG BOLA MENGGUNAKAN KAKI BAGIAN DALAM - Novaldi Kaerala; Nolfie Piri; M.A.S.F Rambitan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
This research aims to test the application of the command teaching style in improving the basic movement ability of kicking the ball with the inside of the foot in the game of soccer. The method used in this research is the experimental method. The samples used were 2023/2024 GPDI Berea Tondano Ajaran Middle School students, totaling 20 samples. The results of this study show that the average increase in the basic movement ability of kicking the ball with the inside of the foot in the experimental group's soccer game using the command teaching style was better than the average increase in the basic movement ability in kicking the ball with the inside of the foot in the control group's soccer game. who did not receive treatment. The conclusion of this research is that there is an influence of the application of the command teaching style on improving the basic movement ability of kicking the ball with the inside of the foot in the game of soccer for GPDI Berea Tondano Middle School students.